ParaHydrogen Polarized Ethyl‐[1‐13C]pyruvate in Water, a Key Substrate for Fostering the PHIP‐SAH Approach to Metabolic Imaging. Issue 11 (7th May 2021) - Carrera, Carla; Cavallari, Eleonora; Digilio, Giuseppe; Bondar, Oksana; Aime, Silvio; Reineri, Francesca
Abstract: An efficient synthesis of vinyl‐[1‐ 13 C]pyruvate has been reported, from which 13 C hyperpolarized (HP) ethyl‐[1‐ 13 C]pyruvate has been obtained by means of ParaHydrogen Induced Polarization (PHIP). Due to the intrinsic lability of pyruvate, which leads quickly to degradation of the reaction mixture even under mild reaction conditions, the vinyl‐ester has been synthesized through the intermediacy of a more stable ketal derivative. 13 C and 1 H hyperpolarizations of ethyl‐[1‐ 13 C]pyruvate, hydrogenated using ParaHydrogen, have been compared to those observed on the more widely used allyl‐derivative. It has been demonstrated that the spin order transfer from ParaHydrogen protons to 13 C, is more efficient on the ethyl than on the allyl‐esterdue to the larger J‐couplings involved. The main requirements needed for the biological application of this HP product have been met, i. e. an aqueous solution of the product at high concentration (40 mM) with a good 13 C polarization level (4.8 %) has been obtained. The in vitro metabolic transformation of the HP ethyl‐[1‐ 13 C]pyruvate, catalyzed by an esterase, has been observed. This substrate appears to be a good candidate for in vivo metabolic investigations using PHIP hyperpolarized probes. Abstract : 13C hyperpolarized ethyl‐[1‐13C]pyruvate by means of PHIP‐SAH : Vinyl‐[1‐ 13 C]pyruvate has been prepared on laboratory scale through a new synthesis route. After its hydrogenation with p‐H2 and magnetization transfer (via MFC), polarized ethyl‐[1‐ 13 C]pyruvate has been obtained in aqueous solution at high concentration (40 mM) and good polarization level (4.8 %). In the end, the in‐vitro conversion of HP ethyl‐[1‐ 13 C]pyruvate into [1‐ 13 C]pyruvate catalysed by an esterase, has been observed.